To solve the equation for y, you need to isolate the variable y.
Multiply both sides of the equation by (5y + 3) to get rid of the denominator on the left side:
−1/(5y + 3) * (5y + 3) = −7 * (5y + 3)
On the left side, the (5y + 3) terms cancel each other out, leaving -1:
-1 = −7 * (5y + 3)
Now, distribute the -7 on the right side:
-1 = -35y - 21
Add 35y to both sides to get the variable term on one side:
35y - 1 = -21
Add 1 to both sides:
35y = -20
Divide both sides by 35:
y = -20/35
This can be simplified to:
y = -4/7
Therefore, the solution to the equation is y = -4/7.
Solve the equation for y.
−1 over 5y+3=−7
1 answer